2003
DOI: 10.1113/eph8802592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Perfusion of Glucagon on Renal Blood Flow in Conscious Sheep

Abstract: The effect of glucagon on renal haemodynamics in sheep is controversial. In this study we have examined the effects of perfused glucagon on renal blood flow (RBF) in six conscious sheep bilaterally implanted with transit‐time ultrasonic flow metering probes around the renal arteries. Glucagon was perfused intravenously over 90 min at doses of 3.12, 6.25, 12.5, 25, 50 and 100 ng kg−1 min−1. Mean RBF was calculated over 10 min periods. Blood samples were taken to monitor the time course of the changes in glycaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Glucagon should not be excluded as a possible mediator considering a. that the circadian rhythm of its pancreatic release depends on feeding behaviour in monogastric animals (Ruiter et al, 2003), b. that amino acids increased the glucagonaemia in sheep (Kuhara et al, 1991) and c. that the intravenous infusion of physiological doses of glucagon induced a highly sensitive dose-dependent increase in RBF in sheep (Denis et al, 2003). In anyway, it must be kept in mind that present results cannot be extrapolated to grazing sheep because of their natural continuous feeding behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon should not be excluded as a possible mediator considering a. that the circadian rhythm of its pancreatic release depends on feeding behaviour in monogastric animals (Ruiter et al, 2003), b. that amino acids increased the glucagonaemia in sheep (Kuhara et al, 1991) and c. that the intravenous infusion of physiological doses of glucagon induced a highly sensitive dose-dependent increase in RBF in sheep (Denis et al, 2003). In anyway, it must be kept in mind that present results cannot be extrapolated to grazing sheep because of their natural continuous feeding behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon exerts a positive effect on renal blood flow and glomerular filtration rate, and increases sodium, chloride, potassium, and inorganic phosphorus clearance ratios (Elrick et al 1958, Bailly et al 1980, Denis et al 2003. No major alterations in renal function have been described in Gcgr K/K mouse models.…”
Section: Role Of Glucagon In Renal Blood Flowmentioning
confidence: 99%
“…A possible explanation for this is that the meal-associated increase in RBF could be determined not only by insulin, but also by other vasoactive substances with possible additive effects, such as glucagon, another important glucoregulatory hormone in ruminants. It has been shown that in sheep fed 1 to 3 times daily, plasma glucagon increased af-ter meals (Bassett, 1972;Mineo et al, 1990), and in a previous work, we found that glucagon infusions at physiological doses elicited dose-dependent increases in sheep RBF (Denis et al, 2003). In spite of the known insulin-induced sympathetic activation in both animals and humans (reviewed by Scherrer and Sartori, 1997), HI infusion did not Increase blood pressure, probably because the sympathetic pressor effects were offset by peripheral vasodilatation, as proposed in dogs (Reikerâs and Gunnes, 1986) and humans (Scherrer et al, 1994).…”
Section: Perfusionsmentioning
confidence: 85%
“…After experimental procedures, the implanted probes were validated for zero blood flow and calibrated in situ to verify the identity between the real (pumped) and the measured flows, according to the method of D' Almeida et al (1995) and described in a previous work (Denis et al, 2003). If necessary, measured flows were corrected for the slight difference between the true and the read flow rate during calibration.…”
Section: Surgical Preparation and Recordingsmentioning
confidence: 99%